6x-3G=9

Simple and best practice solution for 6x-3G=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3G=9 equation:


Simplifying
6x + -3G = 9

Reorder the terms:
-3G + 6x = 9

Solving
-3G + 6x = 9

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-3G + 6x + -6x = 9 + -6x

Combine like terms: 6x + -6x = 0
-3G + 0 = 9 + -6x
-3G = 9 + -6x

Divide each side by '-3'.
G = -3 + 2x

Simplifying
G = -3 + 2x

See similar equations:

| 3x^5-7x+2x^6= | | x^2=-36+12x | | 3.5x=3x+10 | | 8(2.5-3/4)-20=a | | 2(a-3)=5(4-3a) | | 8(2.5-3/4)-20= | | m^2-24=5m | | -(0.75)y=-0.625 | | (2z-7)(-1z+3)= | | 3x^2-8=100 | | 2(x+3)(x-1)=234 | | x^2-24x=-44 | | (-1p+2)(3p^2+1)= | | 3(4.8)+y=3y | | 3t-3+2t=7t-15 | | 3.4q-5.6-3.2q=-0.8q-3.9 | | 144=x(x+2)3 | | (6-5n)(6+5n)= | | 5*(2b-14)=5*b+1 | | 4b^2-8b=0 | | 6i^28=6 | | 2*m+11=4*m*11 | | 85x+1.10x=280 | | 6i^28=i | | 15x+5(.75x)=90 | | 6i^28=x | | 85x+280+1.10x=0 | | 8x^3+6x^2+x=0 | | (1b-8)(5b-2)= | | 15x+5y=90 | | (B-8)(5b-2)= | | 7(9x)+4= |

Equations solver categories